2020
DOI: 10.1101/2020.07.28.225557
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Linking minimal and detailed models of CA1 microcircuits reveals how theta rhythms emerge and how their frequencies are controlled

Abstract: The wide variety of cell types and their inherent biophysical complexities pose a challenge to our understanding of oscillatory activities produced by cellular-based computational models. This challenge stems from the high-dimensional and multi-parametric nature of these systems. To overcome this issue, we implement systematic comparisons of minimal and detailed models of CA1 microcircuits that generate intra-hippocampal theta rhythms (3-12 Hz). We leverage insights from minimal models to guide detailed model … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 66 publications
3
11
0
Order By: Relevance
“…We consider this to be a third building block feature for theta rhythm generation. Further, for the model output to be consistent with experimental observations of excitatory postsynaptic current (EPSC) and inhibitory postsynaptic current (IPSC) amplitude ratios, we found that the connection probability from PV+ to PYR cells was required to be larger than from PYR to PV+ cells—a particular prediction that has been examined and found to be consistent with empirically derived connectivities (Chatzikalymniou et al, 2020 ).…”
Section: A Design Of Microcircuit Models That Produce Theta Rhythmssupporting
confidence: 81%
See 1 more Smart Citation
“…We consider this to be a third building block feature for theta rhythm generation. Further, for the model output to be consistent with experimental observations of excitatory postsynaptic current (EPSC) and inhibitory postsynaptic current (IPSC) amplitude ratios, we found that the connection probability from PV+ to PYR cells was required to be larger than from PYR to PV+ cells—a particular prediction that has been examined and found to be consistent with empirically derived connectivities (Chatzikalymniou et al, 2020 ).…”
Section: A Design Of Microcircuit Models That Produce Theta Rhythmssupporting
confidence: 81%
“…However, since a detailed, biophysical CA1 network model that includes PYR cells and eight different inhibitory cell types has been created (Bezaire et al, 2016 ), one can consider using it as a proxy for the actual biological system to start to explore this. We have done this by bringing together the described microcircuit model used herein and the detailed, full-scale CA1 microcircuit model, and examined how the theta network frequency produced by the detailed model depends on the net input received by the PYR cells (Chatzikalymniou et al, 2020 ). We found that the biologically detailed models strongly support this dependence and thus our proposed hypothesis for theta rhythm frequency control.…”
Section: Discussionmentioning
confidence: 99%
“…As already noted above, the initiation of the theta rhythm is known to be due to the PYR cell population (Chatzikalymniou et al, 2021). The requirement of recurrent connectivity is shown in FIGURE 2C where connections between PYR cells are removed to reveal the loss of theta rhythms.…”
Section: Dissecting the Theta/gamma Fsm Circuitmentioning
confidence: 88%
“…We already know from our previous modeling work that theta rhythm expression is possible with a large enough number PYR cells that have some recurrent connectivity (Chatzikalymniou et al, 2021). In that work, we distinguished the PYR cell population, and not any of the inhibitory cell populations, as the theta rhythm initiators.…”
Section: Anatomy Of a Theta Cycle In The Full-scale Model (Fsm)mentioning
confidence: 99%
See 1 more Smart Citation